2009
DOI: 10.1017/s0950268809991051
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and farm-management-associated variation in the faecal-pat prevalence ofCampylobacter jejuniin ruminants

Abstract: SUMMARYIn a 2-year longitudinal study of adult animals on 15 dairy farms and four sheep farms in Lancashire, UK. C. jejuni was isolated from all farms, although not on every occasion. Faecal samples were collected and cultured using standard techniques for isolation of Campylobacter. Assignment to species was via PCR assays. Peak prevalence of C. jejuni in both cattle and sheep was observed during the summer and in cattle this apparent seasonality was associated with grazing pasture [odds ratio (OR) 2 . 14], w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
46
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 33 publications
7
46
1
1
Order By: Relevance
“…The Campylobacter prevalence in sheep (14.0%) was generally lower than reported elsewhere (range, 17 to 29.3%) (17,35,41,47). This study appears to agree with the true seasonal variation reported to exist in sheep, where the highest prevalence was recorded during the summer months (17).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The Campylobacter prevalence in sheep (14.0%) was generally lower than reported elsewhere (range, 17 to 29.3%) (17,35,41,47). This study appears to agree with the true seasonal variation reported to exist in sheep, where the highest prevalence was recorded during the summer months (17).…”
Section: Discussionsupporting
confidence: 85%
“…For example, feedlot cattle have previously been reported to show a higher prevalence than those on pasture (14), which is likely a result of increased exposure between animals in housing (4,29). However, contradicting this, dairy cattle had the highest prevalence during summer when grazing as opposed to when they were housed during the winter months (17). The presence of seasonal variation in dairy cattle is further supported by the work of Kwan et al (25).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The prevalence of Arcobacter spp. in the sheep samples in this study was 40% (n ϭ 10), which is higher than found in a previous study in the United Kingdom, which isolated Arcobacter using the Campylobacter-specific method, CC (10). Season, climate, geographical location, and sampling and isolation methods may all contribute to the low prevalence of Arcobacter recovered from sheep.…”
Section: Discussioncontrasting
confidence: 71%
“…Higher rates were recorded from chicken giblets (23·5%) compared to duck (19%), turkey (14·5%) and squab (4%) [25]. Previous studies in other countries have also identified C. jejuni as the most common isolate in poultry with C. coli being more frequently isolated from pigs and sheep [14,[26][27][28][29]. Generally, the population of pigs in Egypt is much lower than the poultry populations due to the popular consumption of poultry and the large-scale government culling of around 300 000 pigs during the 2009 H1N1 'swine flu' pandemic [30].…”
Section: Discussionmentioning
confidence: 99%